2000
DOI: 10.1016/s0014-5793(00)01888-3
|View full text |Cite
|
Sign up to set email alerts
|

Amyloids protect the silkmoth oocyte and embryo

Abstract: Chorion is the major component of silkmoth eggshell. More than 95% of its dry mass consists of proteins that have remarkable mechanical and chemical properties protecting the oocyte and the developing embryo from a wide range of environmental hazards. We present data from electron microscopy (negative staining and shadowing), X-ray diffraction and modeling studies of synthetic peptide analogues of silkmoth chorion proteins indicating that chorion is a natural amyloid. The folding and self-assembly models of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
173
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 31 publications
13
173
0
2
Order By: Relevance
“…These data, combined with the fact that silkmoth chorion consists of fibrils similar in appearance to the amyloid fibrils formed from peptide analogues of parts of chorion proteins and structural data of silkmoth chorion presented elsewhere, 7 probably suggest that silkmoth chorion is a natural, protective amyloid that is important for the survival and development of the oocyte and the developing embryo. 7,8 This role is in contrast to that of amyloids associated with serious diseases including Alzheimer's disease, transmissible spongiform encephalopathies, type II diabetes mellitus, and a number of systemic polyneuropathies. 9 -12 Recently, IR, FT-Raman and UV spectroscopy were used to study the binding of Congo red to deposits of Alzheimer's amyloid in cerebral tissue and other typical ␤-amyloid proteins.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…These data, combined with the fact that silkmoth chorion consists of fibrils similar in appearance to the amyloid fibrils formed from peptide analogues of parts of chorion proteins and structural data of silkmoth chorion presented elsewhere, 7 probably suggest that silkmoth chorion is a natural, protective amyloid that is important for the survival and development of the oocyte and the developing embryo. 7,8 This role is in contrast to that of amyloids associated with serious diseases including Alzheimer's disease, transmissible spongiform encephalopathies, type II diabetes mellitus, and a number of systemic polyneuropathies. 9 -12 Recently, IR, FT-Raman and UV spectroscopy were used to study the binding of Congo red to deposits of Alzheimer's amyloid in cerebral tissue and other typical ␤-amyloid proteins.…”
Section: Introductionmentioning
confidence: 56%
“…6 We have recently shown that peptide analogues, both of the entire central domain of the A family of silkmoth chorion proteins (cA peptide) and a part of the central domain of the B family of silkmoth chorion proteins (B peptide), form amyloid-like fibrils by self-assembly mechanisms under a great variety of conditions in vitro. 7,8 The fibrils, ϳ100 Å in diameter (Fig. 1), bind Congo red and show the red-green birefringence characteristic for amyloids, when seen under crossed polars (data not shown).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations